Vietnamese Traditional Narratives as Ecological Parables Promoting an Ecological Ethos - Le Duc, Anthony (Studia Ecologiae et Bioethicae, 2025)
This paper explores the ecological dimensions of Vietnamese traditional narratives (folktales, legends, and myths), arguing that they function as ecological parables that encode moral, spiritual, and practical lessons about humanity’s relationship with the natural world. While ecocriticism has examined the ecological themes in various literary traditions, the ecological insights within Vietnamese folklore remain largely unexplored. This study addresses that gap by conducting an ecocritical reading of nine widely known Vietnamese narratives. These stories are interpreted not only as cultural texts but also as pedagogical tools that promote an ecological ethos rooted in relationality, stewardship, balance, and reverence for the natural world. The analysis draws on Claude Lévi-Strauss’s structuralist theory and insights from ecocritical perspectives to uncover how these narratives reflect and shape human-nature relationships. The paper discusses the potential of these narratives to foster ecological consciousness and offers suggestions for recontextualizing them as tools for promoting environmental ethics and sustainability in contemporary contexts.